2018
DOI: 10.4236/psych.2018.915171
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grit in Education: A Systematic Review

Abstract: Grit is a non-cognitive factor that has received increased attention lately, since research indicates that it plays a significant role in successful outcomes in many fields, and more specifically in education. Grit is rooted in two facets, perseverance of effort and consistency of interest, captured by the Grit Scale. The current systematic review aimed at investigating the association of grit with positive educational outcomes, by exploring both antecedents and outcomes of grit. We identified 29 studies asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 39 publications
2
61
0
7
Order By: Relevance
“…This is coherent with critics who have been skeptical and have downplayed the assumed major benefits of grit for success (Kohn, 2014; Rose, 2013). For instance, a recent overview of the empirical literature showed that students’ grit did not surpass other predictors, such as intelligence or personality traits, for academic performance (Christopoulou, Lakioti, Pezirkianidis, Karakasidou, & Stalikas, 2018). Our study also shows that a satisfactory progression toward an objective does not correspond to the linear accumulation of “good” determinants.…”
Section: Discussionmentioning
confidence: 99%
“…This is coherent with critics who have been skeptical and have downplayed the assumed major benefits of grit for success (Kohn, 2014; Rose, 2013). For instance, a recent overview of the empirical literature showed that students’ grit did not surpass other predictors, such as intelligence or personality traits, for academic performance (Christopoulou, Lakioti, Pezirkianidis, Karakasidou, & Stalikas, 2018). Our study also shows that a satisfactory progression toward an objective does not correspond to the linear accumulation of “good” determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the need for further in-depth domain-specific investigations of grit in language learning, attention to the developmental and growing nature of the construct is inevitable. Admittedly, within the last decade, the bulk of grit-related studies have been criticized for neglecting the situational and context-specific nature of the construct ( Christopoulou et al, 2018 ). Very recently, putting emphasis on the dynamic nature of L2 grit, having examined L2 grit longitudinally, Alamer (2021) found that initial level of L2 grit could not explain later variance of achievement in L2 vocabulary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…are equally important for the success. Grit is a non-cognitive skill [5] which is a pertinent factor in the life of adolescents to make their task complete without interruption. It's necessary to be firm and have a goaloriented approach toward life to achieve long-term and meaningful goals.…”
Section: Viewpoint Of Gritmentioning
confidence: 99%
“…As there are various people likeathletes, students, lawyers are considered to be the gritty people because they require a prolonged commitment and enthusiasm to get success in their goals. Therefore, adolescents need to be diligent, zealous, and prepare themselves in such a way that they can overcome the obstacles for completing the task [3] Grit is considered to be an important factor in accomplishing academics, careers, even in the wellness of emotions [4] It is considered to be the performance character strengths [5] which boost the potential of the students in facing the hardships. Though Grit has been considered as a distinguished quality in various fields as it necessitates being daunting and maintained endeavor despite the greatest failure and hardships [6].…”
Section: Introductionmentioning
confidence: 99%